ESB Integration Patterns an insider's look into SOA's implementation backbone. - Chappell, Dave
The past several years have seen some significant technology trends, such as service-oriented architecture (SOA), enterprise application integration (EAI), business-to-business (B2B) and Web services. These technologies have attempted to address the challenges of improving the results and increasing the value of integrated business processes, and have garnered the widespread attention of IT leaders, vendors and industry analysts. The enterprise service bus (ESB) draws the best traits from these and other technology trends to form a new architecture for integration. The ESB concept is a new approach to integration that can provide the underpinnings for a loosely coupled integration network that can scale beyond the limits of a hub-and-spoke EAI broker.